Comparative Legal Research on Contract Law Changes Under Covid-19 Pandemic: England, United States, Asia and Ukraine - Inna Vorotyntseva; Ivanna Hranina; Maryna Pysarenko (Universidad Hemisferios, 2021)
The study aims to characterize the changes in contract law under the influence of the Covid-19 pandemic in Ukraine and the world. For this purpose, we used systemic, comparative-legal, and formal-legal methods. The paper consists of an introduction, methodology section, bibliography review, results, discussion, conclusions, and references. In the result of the study some distinctive features of changes in contract law under Covid-19 pandemic at the level of national law of Ukraine and some foreign countries were characterized and highlighted. The authors came to the conclusion that changes in contract law are typical for the countries of continental law. Instead, common law states remain resistant to changes in contract law, particularly, the force-majeure application. The reason for this lies in the specific doctrine of the common law countries, as England and the United States. These countries’ courts remain unshakable in terms of managing the contracts performance. In contrast, some Asian and European states (including Ukraine) are characterized by dynamic changes in legislation, given the pandemic situation. The paper also discusses similar institutions like hardship and frustration of purpose, which are both applicable in continental and common law countries.